Classic and new strategies for the treatment of advanced melanoma and non-melanoma skin cancer - Rubatto, Marco; Sciamarrelli, Nadia; Borriello, Silvia; Pala, Valentina; Mastorino, Luca; Tonella, Luca; Ribero, Simone; Quaglino, Pietro (Frontiers in Medicine, 2023)
Advanced melanoma and non-melanoma skin cancers (NMSCs) are burdened with a dismal prognosis. To improve the survival of these patients, studies on immunotherapy and target therapies in melanoma and NMSCs are rapidly increasing. BRAF and MEK inhibitors improve clinical outcomes, and anti-PD1 therapy demonstrates better results than chemotherapy or anti-CTLA4 therapy in terms of the survival of patients with advanced melanoma. In recent years, the combination therapy of nivolumab plus ipilimumab has gained ground in studies for its survival and response rate benefits in patients with advanced melanoma. In addition, neoadjuvant treatment for stages III and IV melanoma, either as monotherapy or combination therapy, has recently been discussed. Another promising strategy evaluated in recent studies is the triple combination of anti-PD-1/PD-L1 immunotherapy and anti-BRAF plus anti-MEK targeted therapy. On the contrary, in advanced and metastatic BCC, successful therapeutic strategies, such as vismodegib and sonidegib, are based on the inhibition of aberrant activation of the Hedgehog signaling pathway. In these patients, anti-PD-1 therapy with cemiplimab should be reserved as the second-line therapy in case of disease progression or poor response. In patients with locally advanced or metastatic SCC, who are not candidates for surgery or radiotherapy, anti-PD1 agents such as cemiplimab, pembrolizumab, and cosibelimab (CK-301) have shown significant results in terms of response rate. PD-1/PD-L1 inhibitors, such as avelumab, have also been used in Merkel carcinoma, achieving responses in half of the patients with advanced disease. The latest prospect emerging for MCC is the locoregional approach involving the injection of drugs that can stimulate the immune system. Two of the most promising molecules used in combination with immunotherapy are cavrotolimod (a Toll-like receptor 9 agonist) and a Toll-like receptor 7/8 agonist. Another area of study is cellular immunotherapy with natural killer cells stimulated with an IL-15 analog or CD4/CD8 cells stimulated with tumor neoantigens. Neoadjuvant treatment with cemiplimab in CSCCs and nivolumab in MCCs has shown promising results. Despite the successes of these new drugs, the new challenges ahead will be to select patients who will benefit from these treatments based on biomarkers and parameters of the tumor microenvironment.